Cellular Assays with a Molecular Endpoint Measured by SAMDI Mass Spectrometry. Issue 28 (30th May 2016) - Berns, Eric J.; Cabezas, Maria D.; Mrksich, Milan
Abstract : Cell‐based, high‐throughput screening (HTS) assays are increasingly important tools used in drug discovery, but frequently rely on readouts of gene expression or phenotypic changes and require development of specialized, labeled reporters. Here a cell‐based, label‐free assay compatible with HTS is introduced that can report quantitatively on enzyme activities by measuring mass changes of substrates with matrix‐assisted laser desorption/ionization mass spectrometry. The assay uses self‐assembled monolayers to culture cells on arrays presenting substrates, which serve as reporters for a desired enzyme activity. Each spot of cells is treated with a compound, cultured and lysed, enabling endogenous enzymes to act on the immobilized peptide substrate. It is demonstrated that the assay can measure protein tyrosine phosphatase (PTP) activity from as few as five cells and a screen is described that identifies a compound that reduces PTP activity in cell lysates. This approach offers a valuable addition to the methods available for cell‐based screening. Abstract : A cell‐based, enzyme activity assay compatible with high‐throughput screening is described, in which cells are cultured on arrays of self‐assembled monolayers presenting enzyme substrates. Cell lysis on the chip enables enzymes to modify the immobilized substrates, changing their mass, which is measured by matrix‐assisted laser desorption/ionization mass spectrometry, detecting activity from as few as five cells.